The use of information technologies in suicide prevention - Jorge, B.; Oliveira, A. (ICERI2021 Proceedings, 2021)
Mental health has become a widely discussed topic. The demystification of this theme has grown exponentially. Also due to the pandemic situation that the world is currently facing, we have been observing a rise in deaths caused by suicide and the numbers do not show signs of a possible reduction. Thus, there is an urgent need to understand the existing methods of suicide prevention, in an accessible and quick way to everyone through information technologies, especially online applications. In this case, we aim to ease the search for these technologies – and systematize them, highlighting their use in suicide prevention –, but also to understand what else can be done to promote them to help possible victims and their families. It sums up what previous authors investigated about suicide prevention through information technologies. Focused on our research question – In what way and with what means may information technologies contribute to suicide prevention? –, a deep analysis of the literature was conducted, in a study covering 50 indexed papers – published from 2007 to 2021 – approaching the use of technologies in suicide prevention, using Leximancer platform, to determine and shape the main themes and concepts proposed in the prevention of suicide – through information technologies papers – and determine how to go further. Our findings give an important contribution to health education, particularly in the prevention of self-destructive behaviors.